OCCURRENCE OF THE SACRED CHANK, XANCUS PYRUM (LINNAEUS) OFF PORTO NOVO - Pillai, P K Mahadevan; Devadoss, P (Indian Journal of Fisheries, 2011)
The sacred chank, Xancus pyrum (Linnaeus) is an important gastropodexploited commercially in a few maritime states in India; the major portionis from Gulf of Mannar and Palk Bay. Nayar and Mahadevan (1973) gavethe details of chank resources of India suggesting possibilities of exploiting themfrom unfished waters